DA'WAH STRATEGIES IN TRANSFORMING THE PERCEPTION AND LIFESTYLE OF PUNK YOUTH: AN ANALYTICAL STUDY OF SURAH AN-NAHL VERSE 125 - Hamid, Abdul (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
The phenomenon of punk youth as an urban subcultural group often marginalized by society presents a unique challenge in the realm of moral and spiritual development. This study aims to explore in depth the da'wah strategies based on the values of Surah An-Nahl verse 125, emphasizing the principles of ḥikmah (wisdom), mauʿiẓah ḥasanah (good advice), and mujādalah (constructive dialogue). Employing a qualitative approach through a case study strategy, data were collected via in-depth interviews, participatory observation, and documentation of da'wah practices targeted at punk communities in urban settings. The findings reveal that an empathetic, inclusive, and contextualized approach to da'wah can foster perceptual shifts regarding religion and behavioral transformation toward positive patterns. Moreover, the integration of Qur'anic values with local cultural expressions proves effective in bridging communication between da'i and madʿū. Sustained, community-based mentoring emerges as a key factor in successfully nurturing new religious identities among individuals previously resistant to religious symbols and narratives. This study contributes a conceptual framework for developing transformative da'wah models that are responsive to the needs of marginalized communities and offers practical implications for building more adaptive, participatory, and spiritually authentic da'wah programs.